The effects of proprioceptive neuromuscular facilitation stretching on shoulder range of motion in overhand athletes - Decicco, P. V.; Fisher, M. M. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of this study was to compare the effects of the contract-relax-contract (CRC) and hold-relax-contract (HRC) proprioceptive neuromuscular facilitation (PNF) stretching programs against a control, on external range of motion (ROM) of the shoulder in apparently healthy athletes. Methods: The subjects were male and female adults between the ages of 25 to 50 years old. Subjects also had been involved in at least one overhand throwing sport (tennis, baseball, quarterback in football, etc.) in the past year. There were 30 participants whom were randomly assigned to 1 of 3 groups (CRC PNF, HRC PNF, control) with 10 subjects per group. Measurement of ROM for external rotation of the shoulder was performed prior to and after 6 weeks of training using a goniometer. The CRC and HRC PNF stretches were performed on subjects twice a week for 6 weeks. The statistical analysis conducted involved a 3¥2 analysis of variance with the criteria for statistical significance set at p<0.05. Post hoc testing included paired t-tests and Tukey tests to pinpoint significant differences relative to the interaction between group and time. Results: There was an increase in ROM from pretest to post-test for the HRC group (+13.50°) and CRC group (+14.60°), but not in the control group (+0.30°). The improvement in ROM however, was similar between the HRC and CRC groups. Conclusion: The CRC and HRC PNF stretching techniques are effective at increasing external shoulder ROM when consistently performed 2 times a week for 6 weeks.